Khulu' Divorce Between Maslahat and Mudharat: A Study on the Sambas Community of the Indonesia-Malaysia Border of West Kalimantan - Asman; Mohammad Aamer (Faculty Sharia of State Islamic University (UIN) Palangka Raya, 2024)
This study discusses the khulu' divorce in sambas between maslahat and mudharat: a study on the Indonesia-Malaysia border community of West Kalimantan. This research was studied based on maslahat and mudaharat. According to qaul jadid, the school of Imam Shafi'i Khulu is also called talaq ba'in shughra where the husband is not allowed to reconcile with his wife during the period of iddah and the husband needs a new marriage contract to return to the wife who has mentalized with khulu'. In order for this research to be directed and systematic, the subject matter is developed in the research question, namely: What are the aspects of benefit and musty mudharat khulu' wives to husbands perspective in Sambas? This type of qualitative research is field research with an Islamic legal approach. The informant in this study is the Malay Sambas community who are divorce perpetrators. Based on the results of the research obtained, the cause of khulu' between maslahat and mudhrat in Sambas based on data obtained from the Sambas Malay community is known that the average age of divorce plaintiffs is more dominant at the age of 26 to age 35 and age 25 and below which is a percentage of 50% and 30%. Based on these data, the divorce rate that occurred in the Class 1B Religious Court of Sambas Regency was dominated by cases of wives filing lawsuits against their mothers. 60-80% of divorce cases that occur from khulu', the wife bandaging files a lawsuit among others (1) economic problems of the household so that the wife is not fulfilled her rights, continuous alterations and quarrels so that the wife cannot stand the situation and the husband leaves his wife and children for no reason so that there is no news so that the wife feels unnoticed. (2) There is a shift in times or lifestyles where the values of marital justice are no longer applied in marriage such as ignoring religious rules, knowing the law but not obeying the law only as a formality so that it is easy to divorce, (3) involvement of the Legal Aid Institute (LBH) and the Legal Aid Post (POSBAKUM) in the divorce process of married couples for divorce.